The Gender of Trees and Their Relationship: Towards the Dendromythology - Razauskas, Dainius (Tautosakos darbai, 2016)
The article consists of two parts. In the first part, the gender of trees emerging in the folk traditions, primarily in the Baltic and Slavic ones, and generally depending on the grammatical form of the denomination of a particular tree is considered. Subsequently, some mythological and ritual materials are presented in the second part of the article, according to which the “female” and “male” trees have sexual relations, mate, and wed. This, on the one hand, amounts to an introduction into the general dendromythology; while on the other hand, it serves to argue that in traditional texts, there is no unbridgeable gap between “purely” poetic metaphor and the corresponding mythological and ritual imagery
Keywords: -